Cuba and the Covid-19 pandemic. (1st June 2021) - Oram, Bob
Abstract : For the UK struggling to deal with the Covid-19 pandemic, the experience of Cuba's Ministry of Public Health over the past six decades provides the clearest case for a single, universal health system constituting an underlying national grid dedicated to prevention and care; an abundance of health professionals, accessible everywhere; a world-renowned science and biotech capability; and an educated public schooled in public health. All this was achieved despite being under a vicious blockade by the United States for all of that time.